2019
DOI: 10.1002/cctc.201901679
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Regioselectivity of Fatty Acid Hydroxylation (C10) at α‐ and β‐Position by CYP152A1 (P450Bsβ) Variants

Abstract: Regioselective hydroxylation on inactivated C−H bonds is among the dream reactions of organic chemists. Cytochrome P450 enzymes (CYPs) perform this reaction in general with high regio‐ and stereoselectivity (e. g. for steroids as substrates). Furthermore, enzyme engineering may allow to tune the properties of the enzyme. Regioselective hydroxylation of shorter or linear molecules (fatty acids), however, remains challenging even with this enzyme class, due to the high similarity of the substrate's backbone carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The G290I mutant plasmid was then used as the template for the next round screening at residues L78 and V170, as both residues contained the second-best hits in the initial screening. The P450 BSβ -L78A mutation was reported to aid the β-selectivity in hydroxylation of decanoic acid (67:33 Cβ/Cα) . We discovered that the double variant, P450 BSβ -L78A/G290I, more effectively boosted the β-regioselectivity (84:7 Cβ/Cα) with 67% conversion (Figure b).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The G290I mutant plasmid was then used as the template for the next round screening at residues L78 and V170, as both residues contained the second-best hits in the initial screening. The P450 BSβ -L78A mutation was reported to aid the β-selectivity in hydroxylation of decanoic acid (67:33 Cβ/Cα) . We discovered that the double variant, P450 BSβ -L78A/G290I, more effectively boosted the β-regioselectivity (84:7 Cβ/Cα) with 67% conversion (Figure b).…”
mentioning
confidence: 88%
“…This highly reactive species then abstracts Cα/Cβ hydrogen atoms of FAs, followed by either an ·OH rebound step to give the respective α/β-OH FAs or a C–C bond scission to yield 1-alkene . Previous search for improved regioselective P450 BSβ variants with hydrophobic amino acid substitutions (Ala, Phe, Val, Leu, Ile, and Trp) and combination of beneficial mutations neither realized a universally satisfying regioselectivity (β-OH/(α-OH+β-OH)<90%) that is sufficient for preparing chiral β-hydroxy FAs nor rationalized the stereochemical outcome of the transformation from a mechanistic perspective . We envisioned that directed evolution of P450 BSβ could possibly remodel its catalytic pathway to favor a predominant Cβ-H abstraction and concurrently shut down the C–C bond scission route, thereby achieving the desired highly regio- and enantioselective β-hydroxylation of fatty acids.…”
mentioning
confidence: 99%
“…15,58,59 In contrast, CYP152A1 shows a preference for the b-position of fatty acids. 15,59,60 On the other hand, CYP152L isozymes mainly perform oxidative fatty acid decarboxylation, producing terminal alkenes, along with aand b-hydroxylation reactions. 61,62 CYP152N1 catalyzes oxidative decarboxylation reaction of fatty acids to produce one-carbon shorter fatty acids.…”
Section: Unspecic Peroxygenases (Upos)mentioning
confidence: 99%
“…As an alternative to NAD(P)H and molecular oxygen, P450s can also utilize hydrogen peroxide (H 2 O 2 ), through the H 2 O 2 ‐shunt pathway. However, this pathway is very inefficient for most P450s, except for the P450s in the CYP152 subfamily 12,13 . In addition, recent studies have shown that the P450 domain of some self‐sufficient monooxygenases can also utilize peroxides for generation of drug metabolites 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this pathway is very inefficient for most P450s, except for the P450s in the CYP152 subfamily. 12,13 In addition, recent studies have shown that the P450 domain of some self-sufficient monooxygenases can also utilize peroxides for generation of drug metabolites. 14,15 Obtaining soluble and stable P450s that can utilize H 2 O 2 has been an appealing target for engineering these enzymes for industrial utilization.…”
Section: Introductionmentioning
confidence: 99%